(untitled) (Cardiovascular Journal, 2021)
Mycobacterium Endocarditis is a very rare case. A 5 years old boy presented us with the history of fever and breathlessness. CXR shows huge cardiomegaly, patient is anemic and temperature is raised. On echo revels vegetation on Tricuspid &Mitral valve ç huge pericardial effusion ç features of early tamponade. Pericardial fluid was drawn and the symptoms improved. Pericardial fluid colour was milky and exudative in nature. ADA for mycobacterium tuberculosis was positive. The patient was given anti tuberculosis drug & improved with time. Cardiovasc j 2021; 14(1): 76-78